Հայ քրդագիտության պատմությունից (Քրդագիտական առաջին գիտաժողովը) - Չաչանի, Կառլեն («Զանգակ - 97»)
In the article there are discussed the role and meaning of the Armenian govemment and the Armenian intelligentsia in the cultural life of the Kurdish people, which brilliantly expressed at All-union Kurdish Studies conference in Yerevan (July 1934). This conference was a historical turning point in the cultural life of the Kurdish people, it concluded and gathered the most great victories of the Kurdish Community in Armenia, which it achieved during several years at the cultural sphere.
Keywords: Պատմություն